Implementation of Online Single Submission (OSS) in the Framework of Acceleration of Business Licensing at the One-Door Integrated Investment and Service Services Office (DPMPTSP) Mandailing Natal - Jureid Jureid; Muhammad Rasyid Siregar; Nur Hanipah Nasution; Nur Azizah; Riski Pardomuan; Ridwanda Sapikri; Candra Husein (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to analyze the implementation of the Online Single Submission (OSS) to accelerate business licensing at the Mandailing Natal Regency Investment and One-Stop Integrated Services Agency (DPMPTSP). The study used a qualitative approach with descriptive methods to in-depth describe the OSS implementation mechanism, supporting and inhibiting factors, and its effectiveness in accelerating licensing services. Data were obtained through in-depth interviews, observation, and documentation. The results show that the implementation of the OSS has significantly changed the licensing service system from a manual pattern to an integrated digital-based system. Issuance of Business Identification Numbers (NIB) for low-risk businesses can be done more quickly than the previous system. However, the acceleration of services is not fully optimal for medium- and high-risk businesses because they still require fulfillment of commitments and additional technical verification. Supporting factors for OSS implementation include regulatory support, apparatus commitment, availability of infrastructure, and increased awareness of business actors. Meanwhile, inhibiting factors include limited internet networks, national system disruptions, low public digital literacy, and administrative constraints. Overall, OSS has contributed to the acceleration of business licensing in Mandailing Natal Regency, but still requires optimization in technical aspects and increasing the capacity of service users.